Rising tuition and enrollment in public higher education - Steven W. Hemelt; Dave E. Marcotte (Institute for the Study of Labor (IZA), 2008)
In this paper we review recent trends in tuition at public universities and estimate impacts on enrollment. We use data from the Integrated Postsecondary Education Data System on all public four-year colleges and universities from 1991 to 2007 and illustrate that tuition increased dramatically beginning in the early part of this decade, increasing at rates unprecedented in the past half century. We examine impacts of these tuition increases on total enrollment and credit hours, and estimate differences by type of institution. We estimate that the average tuition and fee elasticity of total headcount is -0.1072. So, at the mean a 100 increase in tuition and fees (in 2006 dollars) would lead to a decline in enrollment of a little more than 0.25 percent, with larger effects at Research I universities. We find no evidence that especially large increases from one year to the next have a disproportionately large negative effect on enrollment.
urn:nbn:de:101:1-20081127560
Keywords: I2; 330; Higher education; tuition; enrollment; Studienfinanzierung; Hochschule; Studium; Bildungsverhalten; USA